THE CONCEPTS OF DELIBERATIONS AMONGST REPRESENTATIVES IN INDONESIA’S PRESIDENTIAL ELECTION SYSTEM - Khasanofa, Auliya (International Journal of Psychosocial Rehabilitation, 2020)
The change in the constitutional system of Indonesia should ideally follow the concepts of deliberations amongst representatives in line with the philosophy of the country. It should not be the concepts of liberal democracy as reflected in the amendment of the constitution, especially in relation to direct presidential election. This involves the use of liberal democracy which is against the fourth principle of Pancasila (foundational philosophical theory of Indonesia) which states that democracy is guided by the inner wisdom in the unanimity arising from deliberations amongst representatives. The presidential election system is, however, different from the conventional concept which reflects mutual cooperation, not individualism. After the amendment of the UUDNRI, The Constitution of the Republic of Indonesia, Article 6A makes the election of the President and Vice President to be directed by the people and this was observed to affect the basic principles of the 1945 Constitution. This new system is slowly leaving the Pancasila principles which incidentally is the ideology of the country. The problem proposed in this article therefore was, “how is the concept of deliberations amongst representatives in Indonesia’s presidential election system?” The method used was normative and the conclusion proposed are part of the reconstruction efforts to re-implement the concepts of deliberation in the appointment of President by elected representatives through honest and fair general elections.